Use of Whatsapp as A Learning Media to Increase Students' Learning Interest - Sue Holly; Burkewitz Maulik; Irvine Samuel (Yayasan Adra Karima Hubbi, 2023)
The internet and technology are now spreading into the world of Education, including the WhatsApp application. WhatsApp is an application commonly used to communicate remotely, and users can also create groups for friendship between communities in different places. This research aims to find out the benefits of using the WhatsApp application as a learning medium to increase student interest in learning. The method used in this study is quantitative, using a survey model and conducting in-depth interviews. The survey uses Google Forms as a tool for online data collection. The results of this study show that the WhatsApp application can be used as a learning media, as the results are known to researchers when conducting surveys and interviews. The study concludes that the WhatsApp application can be used as a learning medium and supports increasing student interest. The limitations of this study are that researchers only conduct research on the WhatsApp application as a learning medium and only to improve student learning interest.